Early Readers, Scholars and Editors of the New Testament Papers from the Eighth Birmingham Colloquium on the Textual Criticism of the New Testament - Houghton, H. A. G. (Texts and studies, 2014)
The study of the New Testament text is far broader than the reconstruction of its earliest attainable wording. As historical artefacts, manuscripts preserve information about the context in which they were produced and their use in subsequent generations, as well as pointing back towards an earlier stage in the transmission process. References made by Christian authors to the textual culture of the early Church, in addition to their biblical quotations and more general scriptural allusions, transmit information about the treatment of the documents as well as attitudes to (and the form of) the canonical text at the time. The task of the modern textual scholar is as much to map the continuity of the New Testament tradition as to reach behind it for a primitive form which was unknown to most later users.